Efficacy and Safety of Xinyue Capsule for Coronary Artery Disease after Percutaneous Coronary Intervention: A Systematic Review and Meta-Analysis of Randomized Clinical Trials. (9th April 2021) - Jiang, Zhonghui; Qu, Hua; Zhang, Ying; Zhang, Fan; Xiao, Wenli; Shi, Dazhuo; Gao, Zhuye; Chen, Keji
Abstract : To evaluate the efficacy and safety of Xinyue capsule (XYC) in the treatment of coronary artery disease (CAD) after percutaneous coronary intervention (PCI), databases including MEDLINE, EMBASE (Ovid), PubMed, Google Scholar, Cochrane Central Register of Controlled Trials (CENTRAL), China National Knowledge Infrastructure database (CNKI), Wanfang, and VIP were searched to identify randomized controlled trials (RCTs) on XYC in CAD after PCI published before October 2020. Data extraction, methodological quality assessment, and data analysis were performed according to the Cochrane standard. Dichotomous data were shown as risk ratios (RRs) with a 95% confidence interval (CI). All analyses were done with Review Manager, version 5.3. The quality of evidence was assessed by the Grading of Recommendations Assessment, Development and Evaluation (GRADE) approach. A total of 9 related studies from 166 related articles were identified, which included 2979 patients. Compared with conventional treatment alone (or placebo plus), XYC decreased cardiovascular events [RR = 0.37, 95% CI (0.27, 0.51), I 2  = 0%] (nonfatal myocardial infarction [RR = 0.26, 95% CI (0.10, 0.70), I 2  = 0%], revascularization [RR = 0.38, 95% CI (0.24, 0.61), I 2  = 0%], and rehospitalization due to ACS [RR = 0.48, 95% CI (0.33, 0.68), I 2  = 0%]) and improved cardiac function (LVEF [RR = 6.93, 95% CI (4.99, 8.87), I 2  = 81%], LVEDV [RR = −4.07, 95% CI (−5.61, −2.54), I 2  = 7%], and LVESV [RR = −4.32, 95% CI (−5.90, −2.74), I 2  = 50%]) in patients after PCI. In addition, XYC reduced serum NT-pro-BNP [RR = −126.91, 95% CI (−231.51, −22.31), I 2  = 69%]. However, XYC had little effect on cardiovascular death [RR = 0.47, 95% CI (0.13, 1.68), I 2  = 0%], stroke [RR = 0.52, 95% CI (0.23, 1.20), I 2  = 0%], heart failure [RR = 0.53, 95% CI (0.24, 1.20), I 2  = 0%], and quality of life [RR = −1.37, 95% CI (−4.97, 2.22), I 2  = 93%]. Thus, this meta-analysis suggests that XYC has potential advantages in reducing the occurrence of cardiovascular events after PCI, improving cardiac function, and reducing serum NT-pro-BNP. This potential benefit requires a high-quality RCT to assess.